Efficacy of Rivaroxaban for thromboprophylaxis after Knee Arthroscopy (ERIKA) - Camporese, Giuseppe; Bernardi, Enrico; Noventa, Franco; Bosco, Mario; Monteleone, Giuseppe; Santoro, Luca; Bortoluzzi, Cristiano; Freguja, Stefano; Nardin, Michela; Marullo, Matteo; Zanon, Giacomo; Mazzola, Claudio; Damiani, Guido; Maniscalco, Pietro; Imberti, Davide; Lodigiani, Corrado; Becattini, Cecilia; Tonello, Chiara; Agnelli, Giancarlo (Thrombosis and Haemostasis, 2016)
Without thromboprophylaxis, knee arthroscopy (KA) carries a low to moderate risk of venous thromboembolism. Over 5 million arthroscopies are performed worldwide yearly. It was our study objective to assess the efficacy and safety of rivaroxaban for thromboprophylaxis after therapeutic KA. Patients undergoing KA in nine Italian teaching or community hospitals were allocated to once-daily rivaroxaban (10 mg) or placebo for seven days in a phase II, multicentre, double-blind, placebo-controlled randomised trial. The primary efficacy outcome was a composite of all-cause death, symptomatic thromboembolism and asymptomatic proximal DVT at three months; major bleeding represented the primary safety outcome. All patients underwent whole-leg ultrasonography at day 7(+1), or earlier if symptomatic. A total of 241 patients were randomised (122 rivaroxaban, 119 placebo), and 234 completed the study. The primary efficacy outcome occurred in 1/120 of the rivaroxaban group and in 7/114 of the placebo group (0.8% vs 6.1%, respectively, p=0.03; absolute risk difference, −5.3%, 95% CI, −11.4 to −0.8; crude relative risk 0.14, 95% CI, 0.02 to 0.83; number-needed-to-treat=19). No major bleedings were observed. We found no association between different arthroscopic procedures and thrombotic events. Small sample size, high exclusion rate, and low number of anterior cruciate ligament reconstruction procedures are the main limitations of our study. In conclusion, a seven-day course of 10-mg rivaroxaban may be safely employed for thromboprophylaxis after KA. Whether prophylaxis after KA should be given to all patients, or to selected “high-risk” subjects, remains to be determined. A larger trial to verify our preliminary results is warranted.
Keywords: Venous thromboembolism; prophylaxis; arthroscopy; rivaroxaban; bleeding